2013
DOI: 10.2108/zsj.30.360
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Two Androgenetic Clam Species,Corbicula leanaandCorbicula fluminea, Inferred from Mitochondrial Cytochrome b and Nuclear 28S rRNA Markers

Abstract: Two shell color types, yellow (type I) and brown (type II), of hermaphrodite Corbicula fluminea clams from Ritto, Shiga Prefecture, Japan, are sympatric with both male and hermaphrodite Corbicula leana. In the present study, the mitochondrial DNA (mtDNA) cytochrome b and nuclear 28S rRNA genes of C. fluminea were sequenced to construct a haplotype network in order to investigate the genetic relationship with C. leana. Ninety C. fluminea samples revealed only two cytb haplotypes; the majority (97.8%) were CB7, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 14 publications
0
18
0
Order By: Relevance
“…The most unexpected result of the 28S sequencing is the extremely high presence of heterozygotes (162 out of 175). This feature could be due to multiple copies of the 28S gene in the genome (Lee et al, 2005;Komaru et al, 2013). However, cloning results suggested that multi-copy probably explains only the low occurrence of rare haplotypes, while 'true heterozygosity' originated from sexual reproduction should be assumed for the most common alleles.…”
Section: Invasive Lineages' Distribution Based On the 28s Gene Analysismentioning
confidence: 76%
See 3 more Smart Citations
“…The most unexpected result of the 28S sequencing is the extremely high presence of heterozygotes (162 out of 175). This feature could be due to multiple copies of the 28S gene in the genome (Lee et al, 2005;Komaru et al, 2013). However, cloning results suggested that multi-copy probably explains only the low occurrence of rare haplotypes, while 'true heterozygosity' originated from sexual reproduction should be assumed for the most common alleles.…”
Section: Invasive Lineages' Distribution Based On the 28s Gene Analysismentioning
confidence: 76%
“…Only 2 out of the 10 haplotypes (S5, S10) were novel. The remaining eight matched either with our reference haplotypes (S1 = SR1, RA lineage; S6 = SR2, RlcB lineage; S8 = SR4, SC lineage; Table 2), with other haplotypes previously found in invaded regions (S3 corresponded to RA lineage, GenBank accession EU090403; Hedtke et al, 2008), or with Japanese native haplotypes (S2, S4, S7, and S9 matched to Japanese C. fluminea, GenBank numbers AB736282, AB736278, AB736287, and AB736291, respectively; Komaru et al, 2013).…”
Section: Haplotype Distribution and Population Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…Although its invasion and rapid expansion have been of intensive research topic in freshwater ecology, the taxonomy and systematic status of freshwater clam Corbicula in its native range is still not clearly resolved (Park and Kim 2003). Several systematic uncertainties using molecular methods were clarified in the last decades, such as mitochondrial and nuclear marks (Hedtke et al 2008;Komaru et al 2012Komaru et al , 2013. However, it still remained confusing, mainly due to the polymorphism of the morphology, color of the shell, and complex reproduction modes.…”
Section: Introductionmentioning
confidence: 99%